The IMF Strategy for Fragile and Conflict-Affected States. (Policy Papers; Policy Paper ;, 2022)
This paper proposes a comprehensive Strategy to strengthen IMF support to FCS in accordance with the Fund's mandate and comparative advantage. The Strategy is a response to the Board-endorsed recommendations of the 2018 Independent Evaluation Office (IEO) Report on The IMF and Fragile States. To achieve these goals, the Strategy will benefit from additional resources reflected in the FY23-25 Medium-Term Budget, as per the budget augmentation framework discussed by the Board in December 2021. The Strategy also provides measures to better support staff working on FCS. Given the inherent risks in FCS engagement, the Strategy will be phased in starting in FY22, with implementation gradually accelerating between FY23-FY25.